Pengaruh Pelarut dan Metode Ekstraksi terhadap Kandungan Metabolit Sekunder dan Nilai IC50 Ekstrak Umbi Bit (Beta vulgaris L.) - Sasadara, Maria Malida Vernandes; Wiranata, I Gede (Usadha, 2022)
Beetroot (Beta vulgaris L.) contains phenolic, flavonoid, and tannin, as well as anthocyanin and betacyanin pigments which are strong antioxidant compounds. The extraction process is needed to collect the phytochemical content in plant samples. Several factors affect the extract's phytochemical content, including the extraction method and solvent. This research was conducted to determine the effect of maceration and ultrasonic extraction methods and solvents on the levels of phenol, flavonoids, tannins, anthocyanins, and the IC50 value of beetroot extract. This research is experimental laboratory research. Extraction of beetroot was carried out by maceration (M) and ultrasonic (U) using water solvents (MA & UA), 50% ethanol (ME50 & UE50), and 96% ethanol (ME96 & UE96). Phytochemical quantification was carried out on phenols, flavonoids, tannins, and anthocyanins levels. The antioxidant activity test was carried out using the DPPH method to obtain the IC50 value. Data analysis was performed using one-way analysis of variance (ANOVA) with a 95% confidence level. The results showed that the selection of extraction methods and solvents affected the concentration of phenols, flavonoids, tannins, and anthocyanins, as well as the antioxidant activity of the extracts. The UE96 extract produced the highest concentrations of phenols, flavonoids, tannins, and anthocyanins compared to other extracts, with the lowest IC50. All results showed significant differences (p<0.05) except for the anthocyanin content produced by ME96 and UA extracts. In conclusion, the ultrasonic method with 96% ethanol solvent is considered the best method for extracting beetroot (Beta vulgaris L.), producing extract with good antioxidant activity and high levels of phenol, flavonoids, tannins, and anthocyanins.